2018
DOI: 10.7554/elife.37949
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitioned nuclear Oskar promotes cell division of Drosophila primordial germ cells

Abstract: Germ granules are non-membranous ribonucleoprotein granules deemed the hubs for post-transcriptional gene regulation and functionally linked to germ cell fate across species. Little is known about the physical properties of germ granules and how these relate to germ cell function. Here we study two types of germ granules in the Drosophila embryo: cytoplasmic germ granules that instruct primordial germ cells (PGCs) formation and nuclear germ granules within early PGCs with unknown function. We show that cytopla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(118 citation statements)
references
References 101 publications
(262 reference statements)
10
107
1
Order By: Relevance
“…Annuli similar to those formed by acetylated TDP-43 have been reported in Drosophila germ granules, first reported as intranuclear spherical annuli (52) and later shown to be gel-like (53).…”
Section: Discussionmentioning
confidence: 55%
“…Annuli similar to those formed by acetylated TDP-43 have been reported in Drosophila germ granules, first reported as intranuclear spherical annuli (52) and later shown to be gel-like (53).…”
Section: Discussionmentioning
confidence: 55%
“…Germ plasm is a specialized cytoplasm that forms at the embryo's posterior pole and is populated by core granule proteins Oskar, Vasa, Tud and Aub, a variety of RNA‐binding proteins involved in various aspects of RNA biology, maternally deposited mRNAs, piRNAs and mitochondria (Figure A‐D) (reviewed in Reference ). While most of the RNA‐binding proteins enriched in germ plasm are also found elsewhere in the embryo, the core granule proteins are almost exclusively found only at the posterior pole . The exact composition of germ plasm is not known, however, recent quantitative imaging data demonstrated that the vast majority of core germ plasm proteins (>94%) are condensed into granules, with very little of these proteins diffusing in the intergranular germ plasm space .…”
Section: Ontogeny and Organization Of Germplasmmentioning
confidence: 99%
“…While most of the RNA‐binding proteins enriched in germ plasm are also found elsewhere in the embryo, the core granule proteins are almost exclusively found only at the posterior pole . The exact composition of germ plasm is not known, however, recent quantitative imaging data demonstrated that the vast majority of core germ plasm proteins (>94%) are condensed into granules, with very little of these proteins diffusing in the intergranular germ plasm space . Indeed, their concentration in the intergranular space is similar to their concentration in somatic regions .…”
Section: Ontogeny and Organization Of Germplasmmentioning
confidence: 99%
“…However, a different class of multilayered MLOs has also been reported, where the layered topology is manifested due to the presence of a hollow internal space. For example, in vivo experiments have demonstrated that both nuclear and cytoplasmic germ granules of Drosophilla can exhibit hollow morphologies (14)(15)(16). In another system, it was observed that simple overexpression of TDP-43, a stress granule protein, can give rise to multilayered compartments with vacuolated nucleoplasm-filled internal space (17).…”
Section: Introductionmentioning
confidence: 99%